The mediating impact of airlines’ image in relation of corporate social responsibility and customers’ loyalty: An empirical in Vietnam - Hai Phan Thanh; Thu Hoang Anh (Cogent Business & Management)
Corporate social responsibility (CSR) towards sustainable development has been identified as a marketing philosophy that businesses in developed countries should pursue in the post-Covid-19 era as these practices deal with urgent global social and environmental challenges. Such efforts contributing to sustainable development will enhance corporate image and reinforce strong bonds with customers. In developing countries like Vietnam, how CSR affects consumer behaviour and the mechanism regulating the relationship between CSR and consumer behavior are the research gaps that have not been widely investigated. This study explores the relationship between CSR and customer loyalty, with the emphasis on the mediating role of corporate image. Focusing on the Vietnamese aviation industry, the author surveyed 514 passengers and analyzed them using structural equation modeling. Our findings show that CSR has a positive impact on corporate image and customer loyalty. In addition, CSR also affects customer loyalty through enhancing corporate image. Research results have provided research implications and management implications for the future.